Effects of prebiotic (lactoferrin) and diclazuril on broiler chickens experimentally infected with Eimeria tenella - Abd El Monsef, Asmaa G.; El Zohairy, Nermin F.; Hassan, Marwa F.; Salem, Sanaa M.; Gouda, Asmaa Aboelabbas; Mansour, Mogda K.; Alkhaldi, Abdulsalam A. M.; Alzaylaee, Hind; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2024)
Introduction: Avian coccidiosis presents a significant challenge to the poultry industry in Egypt, highlighting the urgent need for validating new drug targets offering promising prospects for the development of advanced anticoccidials. Although numerous reports highlightg the activity of lactoferrin (LF) against various microorganisms, its potential against Eimeria has not been explored. The present study evaluated the potential anticoccidial effect of LF and diclazuril in broiler chickens experimentally infected with Eimeria tenella. Methods: A total of 100 one-day-old broiler chicks were divided into five equal groups (20 each) as follows: Group 1 (G1) served as the normal healthy control group, Group 2 (G2) consisted of chickens infected with 1×105 sporulated E. tenella oocysts at 14 days of age, Group 3 (G3) comprised infected chickens treated with diclazuril (0.5 mL/L in drinking water) for 3 days successively, Group 4 (G4) included infected chickens treated with LF (a dose of 250 mg/kg of diet) from one day of age until the end of the study, and Group 5 (G5) comprised infected chickens treated with both LF and diclazuril. Results: The positive control group (G2) experienced significant reductions in body weight (BW), BW gain, serum glucose, lipase, amylase, total antioxidant capacity, several hematological indices, and total proteins, along with alterations in various antioxidant enzymes. Conversely, serum levels of aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatases (ALP), urea, creatinine, nitric oxide, mean corpuscular volume (MCV), White blood cells (WBCs), heterophils, alpha 2, beta 1, and liver contents of malondialdehyde were elevated in this group. Moreover, higher oocyst counts and lesion scores, along with histopathological alterations, were observed in G2. Remarkably, treatment with diclazuril and/or LF demonstrated potent antioxidant and anticoccidial effects, resulting in reduced shedding of oocysts, lesion scores, and lymphocytic infiltrates in the cecum. Additionally, these treatments improved the antioxidant and immune systems in chickens and restored all histopathological changes reported in the infected non-treated group (G2). Conclusion: This study offers novel perspectives on the potential anticoccidial effects of the combination of LF and diclazuril in broiler chickens infected with E. tenella, highlighting the potential synergistic actions of LF in treating poultry coccidiosis.